MUSIC THERAPY - Sharma, Archana (International Journal of Research -GRANTHAALAYAH, 2015)
Music Therapy is an established health profession in which music is used within a therapeutic relationship to address to physical, emotional, cognitive and social needs of individuals. After assessing the strength and needs of each client, the qualified music therapist provides the indicated treatment including creating, singing, moving to and/or listening to music. Through musical involvement in therapeutic context, clients, abilities are strengthened and transfer to other areas of their lives.